2021
DOI: 10.1007/s11094-021-02387-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Total Flavonoids in Tagetes patula Marigold Flowers

Abstract: Tagetes patula L. (marigold) is a valuable source of biologically active compounds, including flavonoids. A quantitative determination method for total flavonoids in T. patula flowers using differential spectrophotometry at analytical wavelength 428 nm and a reference standard of patulitrin (3,5,7,3¢,4¢-pentahydroxy-6-methoxyflavone 7-O-b-D-glucopyranoside) was developed during the present work. The error of a single determination of total flavonoids in T. patula flowers was ± 3.86% with confidence probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Therefore, it was concluded that marigold extract was a flavonoids. According to Kurkina et al [17], it was reported that the type of flavonoids in Marigold flower was a yellow quercetin as shown in Fig. 4.…”
Section: Physical Characteristics and Types Of Phytochemicals In Mari...mentioning
confidence: 99%
“…Therefore, it was concluded that marigold extract was a flavonoids. According to Kurkina et al [17], it was reported that the type of flavonoids in Marigold flower was a yellow quercetin as shown in Fig. 4.…”
Section: Physical Characteristics and Types Of Phytochemicals In Mari...mentioning
confidence: 99%
“…Previous studies on the volatile substances in the flowers and leaves of marigold have indicated that there is a large proportion of various terpenoids, which produce the terpenes volatile organic compounds (VOCs) ( Ogunwande and Olawore, 2006 ). Few flavone derivatives have been identified in different marigold species, namely, luteolin and luteolin 7-O-glucoside from Tagetes multiflora ( Abdala, 2003 ), and chrysocriol-7-O-(6-O-β-L-arabinofuranosyl)-D-glucopyranoside from Tagetes patula ( Kurkina et al., 2021 ). Similarly, carotenoids, mainly β-carotene and zeaxanthin, were found in Tagetes species ( Breithaupt et al., 2001 ).…”
Section: Introductionmentioning
confidence: 99%